Decadal epidemiological profile of hospital admissions for migraines and headaches in Paraná - Valerio, Catharina Delazari; Miranda, Livia Garcia Hoyer; Tomasi, Gustavo Henrique (Headache Medicine, 2024)
Introduction: Understanding the epidemiology of a prevalent and disabling disease is essential for shaping healthcare policies and service organizations, identifying associated factors, and assessing the health impacts on the population. Therefore, understanding the epidemiology of headaches in Paraná is crucial for developing strategies and public policies for clinical management and prevention of these conditions. Objectives: To outline the epidemiological profile of hospital admissions for migraines and other headache disorders in Paraná from 2014 to 2023.Methodology: This retrospective and analytical study utilized data from the Brazilian Unified Health System's Hospital Information System concerning hospitalizations due to migraines and other headache disorders in Paraná from 2014 to 2023, having no difference between diagnostic categories of painful syndromes. The study included individuals of both genders, aged 15 to 79 years. Results: 13,287 hospitalizations were reported during the study period. Of these, 12,305 (92.6%) were urgent admissions and 982 (7.39%) were elective, with an average length of stay of 2.6 days, totaling R$7,222,753.27 in healthcare costs. Regarding the demographic profile of hospitalized patients, 8,319 (62.61%) were female and 4,968 (37.38%) were male. Among female patients, 574 (6.9%) were aged 15 to 19 years, 1,556 (18.7%) were aged 20 to 29 years, 1,497 (18%) were aged 30 to 39 years, 1,705 (20.5%) were aged 40 to 49 years, 1,443 (17.35%) were aged 50 to 59 years, 1,022 (12.3%) were aged 60 to 69 years, and 522 (6.3%) were aged 70 to 79 years. For male patients, 265 (5.3%) were aged 15 to 19 years, 741 (14.9%) were aged 20 to 29 years, 844 (17%) were aged 30 to 39 years, 935 (18.8%) were aged 40 to 49 years, 950 (19%) were aged 50 to 59 years, 826 (16.6%) were aged 60 to 69 years, and 407 (8.2%) were aged 70 to 79 years. Conclusion: This study provides a comprehensive overview of hospitalizations due to migraines and headaches in Paraná, highlighting the gender and age distribution of affected individuals over a nine-year period. These findings are crucial for developing targeted healthcare interventions and policies aimed at improving clinical management and prevention strategies for these conditions.